2014
DOI: 10.1007/s00442-014-3157-6
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a salt refuge: chytrid infection loads are suppressed in hosts exposed to salt

Abstract: With the incidence of emerging infectious diseases on the rise, it is becoming increasingly important to identify refuge areas that protect hosts from pathogens and therefore prevent population declines. For the chytrid fungus Batrachochytrium dendrobatidis, temperature and humidity refuge areas for amphibian hosts exist but are difficult to manipulate. Other environmental features that may affect the outcome of infection include water quality, drying regimes, abundance of alternate hosts and isolation from ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 51 publications
0
56
0
Order By: Relevance
“…Non‐salted water bodies (“low salinity” treatments) were found to fluctuate between 0 and 1 ppt. These ranges of salt levels in water bodies occupied by L. aurea are observed regularly in the field in natural L. aurea ponds and are within the known physiological limits of the species (Mahony et al., ; Stockwell, Clulow, et al., ). Salinity values were recorded periodically across the study period using a water quality meter (YSI professional plus water meter, Xylem, USA) to measure salt levels, and additional water or salt was added where necessary to maintain the targeted salt concentrations.…”
Section: Methodsmentioning
confidence: 57%
See 3 more Smart Citations
“…Non‐salted water bodies (“low salinity” treatments) were found to fluctuate between 0 and 1 ppt. These ranges of salt levels in water bodies occupied by L. aurea are observed regularly in the field in natural L. aurea ponds and are within the known physiological limits of the species (Mahony et al., ; Stockwell, Clulow, et al., ). Salinity values were recorded periodically across the study period using a water quality meter (YSI professional plus water meter, Xylem, USA) to measure salt levels, and additional water or salt was added where necessary to maintain the targeted salt concentrations.…”
Section: Methodsmentioning
confidence: 57%
“…There is evidence that environmental factors mitigate the biological activity of Batrachochytrium dendrobatidis ( Bd ), the aetiological agent in chytridiomycosis, and as a result the disease dynamics in host populations. The viability and disease impact of the aquatically transmitted Bd may be inhibited and limited by elevated temperature (Forrest & Schlaepfer, ; Johnson, Berger, Phillips, & Speare, ; Piotrowski, Annis, & Longcore, ; Savage, Sredl, & Zamudio, ; Stevenson et al., ) and salinity (Heard, Scroggie, Clemann, & Ramsey, ; Stockwell, Clulow, & Mahony, , ; Stockwell, Storrie, Pollard, Clulow, & Mahony, ). As well, there is evidence that post‐metamorphic stages of some susceptible host species may be cleared of the disease in wild populations (Brannelly et al., ; Briggs et al., , ; Kriger & Hero, ; Murray, Skerratt, Speare, & McCallum, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Karraker and Ruthig (2009) found no interactive effects between high salt and ubiquitous water moulds that infected amphibian clutches. Stockwell, Clulow, and Mahony (2015) actually found that NaCl concentrations >1,213 mg Cl − /L reduced host infection loads of chytrid fungus (Batrachochytrium dendrobatidis) in the eastern dwarf tree frog (Litoria fallax). However, in a recent study, Milotic, Milotic, and Koprivnikar (2017) found that wood frogs exposed to road salt concentrations >360 mg Cl − /L had more helminth parasite cysts and exhibited reduced anti-parasite behaviour compared to concentrations <100 mg Cl − /L.…”
Section: Wetland Communitiesmentioning
confidence: 98%